Influence of the magnetic field on bandgap and chemical composition of zinc thin films prepared by sparking discharge process - Stefan Ručman (2020)
© 2020, The Author(s). We examine the influence of the magnetic field on the chemical reaction of nitrogen and carbon dioxide in sparking electric discharge of zinc wires. Samples are prepared on Indium Tin Oxide (ITO) and quartz substrates in the form of thin films at 0 T, 0.2 T and 0.4 T. Different chemical composition of thin-films prepared by sparking discharge was obtained and verified by XPS, Raman and Cyclic voltammetry. Carbon dioxide conversion to carbonates was observed for zinc sparked in CO2 and nitrogen affecting crystallization of thin films was confirmed by XRD. Synthesis route for thin-film preparation used in this study is electric sparking discharge, convenient for fast ionization of metal and gasses. Band gap energy of thin films prepared by this method was starting from 2.81 eV and 4.24 eV, with the lowest band gaps prepared on ITO in 0.4 T. Dynamic mobility analysis (DMA) indicates smaller particles are fabricated by discharging zinc wires in a higher magnetic field. Nitridification of zinc nanoparticles occurred on 0.2 Tesla magnetic field strength and it was detectable even after XPS ion gun etching. Carbonation and nitridification of zinc thin films by sparking wires inside the magnetic field to observe the effect of the magnetic field on bandgap and chemical composition are confirmed by XPS.